Rhodnius prolixus and R. robustus (Hemiptera: Reduviidae) nymphs show different locomotor patterns on an automated recording system. Issue 1 (December 2016) - Pavan, Márcio; Corrêa-Antônio, Jessica; Peixoto, Alexandre; Monteiro, Fernando; Rivas, Gustavo
Abstract Background Circadian rhythms of triatomines, vectors of the etiological agentTrypanosoma cruzi responsible for Chagas disease, have been extensively studied in adults of the two most epidemiologically relevant vector species, Rhodnius prolixus andTriatoma infestans . However, little attention has been dedicated to the activity patterns in earlier developmental stages, even though triatomine nymphs are equally capable of transmittingT. cruzi to humans. Because circadian rhythms may differ even between closely related species, studies that focus on this behavioral trait can also be used to shed light on the taxonomy of controversial taxa, which becomes especially relevant regarding vector species. Methods We compared the daily locomotor activity patterns of second- and third-instar nymphs ofRhodnius prolixus andRhodnius robustus in order to unveil possible behavioral differences between these cryptic species. Mitochondrial and nuclear markers were sequenced to confirm species identification. Results Nymphs of both species had a bimodal pattern of locomotion and similar daily activity patterns, butR. prolixus is more active under light/dark cycles and depicts a more pronounced activity rhythm under constant darkness conditions. Conclusions We describe the implementation of an often-used automated method for the recording of individual locomotor activity to differentiate sibling species ofRhodnius with distinct epidemiological relevance. The higher levels of activity observed in the nymphs ofR. prolixus could potentially contribute to increased vector capacity.